Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s12311-014-0630-z
|View full text |Cite
|
Sign up to set email alerts
|

Metalinguistic Deficits in Patients with Cerebellar Dysfunction: Empirical Support for the Dysmetria of Thought Theory

Abstract: The cerebellar cognitive affective syndrome (CCAS) includes disruption of linguistic processing such as verbal fluency, verbal working memory, grammar, and speech perception. We set out to examine linguistic capabilities in patients with cerebellar lesions to determine which domains are spared and which impaired and to evaluate the underlying cognitive structure of these deficits. Forty-four patients with cerebellar disease were compared to 40 healthy controls on the Oral Sentence Production Test (OSPT) which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

5
3

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 14 publications
5
54
1
Order By: Relevance
“…34 The peculiar cognitive and behavioral profile in this DRPLA pedigree reflects "dysmetria of thought," which is a key element of cerebellar cognitive-affective syndrome. [35][36][37][38] Neuroimaging in these DRPLA patients demonstrated atrophy of the cerebellum and midbrain at all ages, confirming the presence of cerebral Caucasians matter lesions only in adult and elderly patients 6 ( Supplementary Table 4).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…34 The peculiar cognitive and behavioral profile in this DRPLA pedigree reflects "dysmetria of thought," which is a key element of cerebellar cognitive-affective syndrome. [35][36][37][38] Neuroimaging in these DRPLA patients demonstrated atrophy of the cerebellum and midbrain at all ages, confirming the presence of cerebral Caucasians matter lesions only in adult and elderly patients 6 ( Supplementary Table 4).…”
Section: Discussionsupporting
confidence: 57%
“…The qualitative analysis of drawing indicated by the Qualitative Scoring MMSE Pentagon Test score of the MMSE pentagon copy task also suggested semantic deficits related to the degradation of the mental representation of the figure, rather than graphic visuoperceptual difficulties . The peculiar cognitive and behavioral profile in this DRPLA pedigree reflects “dysmetria of thought,” which is a key element of cerebellar cognitive‐affective syndrome …”
Section: Discussionmentioning
confidence: 79%
“…Identifying and mapping these macro-scale networks in different brain territories is relevant for the characterization of functional and structural abnormalities in psychopathology (Darby et al 2018, Palaniyappan & Liddle 2012, Whitfield-Gabrieli & Ford 2012, and necessary for the development of targeted brain stimulation interventions (Esterman et al 2017). In the specific case of cerebellar cortex, damage to the cerebellar posterior lobe, which provides inputs to the DN, causes the cerebellar cognitive affective syndrome, characterized by deficits in executive, linguistic, visuospatial and affective processing (Guell et al 2015;Hoche et al 2016Hoche et al , 2018Schmahmann & Sherman 1998, Schmahmann et al 2009, Stoodley et al 2016). In addition, multiple studies have reported cerebellar cortical abnormalities in numerous disorders such as Alzheimer's disease (Guo et al 2016, Jacobs et al 2018, autism spectrum disorder (Arnold Anteraper et al 2018, D'Mello & Stoodley 2015, and schizophrenia (Moberget et al 2018), with preliminary evidence suggesting that cerebellar cortical stimulation might improve symptoms in these diseases (Brady et al 2019, Demirtas-Tatlidede et al 2010, Di Lorenzo et al 2013, Garg et al 2016, Stoodley et al 2017, Tikka et al 2015.…”
Section: Relevance For Cerebellar Neuroscience Neurology and Psychimentioning
confidence: 99%
“…Language deficits include abnormal syntax resulting in a grammatism [11, 146]. Discourse, which is the essence of verbal communication, can be disrupted by impaired metalinguistic ability [157]. This manifests as deficits in understanding metaphor, ambiguity, and inferential thinking, and difficulty expressing thoughts verbally.…”
Section: The Cerebellar Cognitive Affective Syndrome (Jeremy D Schmamentioning
confidence: 99%